2018
DOI: 10.15675/gepros.v13i3.1960
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do Overall Equipment Effectiveness (OEE) em células de manufatura considerando o takt time

Abstract: Utilização do Overall Equipment Effectiveness (OEE) em células de manufatura considerando o takt timeDentre as formas de medição e de melhoria da eficiência de processos industriais, destaca-se a utilização do Overall Equipment Effectiveness (OEE) também conhecido como Índice de Eficiência Global. Este indicador de eficiência caracteriza-se por considerar no cálculo os fatores: utilização do tempo disponível; o ritmo; e a qualidade do produto. O OEE tem sido implementado largamente para o controle e melhoria d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The initial installed capacity refers to the highest possible value given the initial standard times that are calculated. From Table 1 it can be concluded that the bottle neck [6] is at the final lathing of the exterior with a maximum of 17 pieces an hour (bold value in Table 1). In order to calculate the OEE, we compare the actual capacity to the maximum possible capacity [7].…”
Section: Calculating Initial Installed Capacity and Oee (Overall Equimentioning
confidence: 99%
“…The initial installed capacity refers to the highest possible value given the initial standard times that are calculated. From Table 1 it can be concluded that the bottle neck [6] is at the final lathing of the exterior with a maximum of 17 pieces an hour (bold value in Table 1). In order to calculate the OEE, we compare the actual capacity to the maximum possible capacity [7].…”
Section: Calculating Initial Installed Capacity and Oee (Overall Equimentioning
confidence: 99%